Nitrogen utilization efficiency by naturally colored cotton cultivars in semi-arid region (Revista Ciência Agronômica, 2020)
Knowledge on nitrogen (N) utilization efficiency in colored cotton enables the correct management of Nfertilizers, optimizing yield and minimizing environmental degradation.The objective of this study was to evaluate the Nutilization efficiency and to determine the accumulation of dry matter and N by naturally colored cotton cultivars subjectedto N fertilization in the Brazilian semi-arid region.The experiment was carried out under field conditions, at the Farm ofthe Federal Rural University of the Semi-Arid, in 2016 and 2017. The experimental design was in randomized blocks withsplit plots and four replicates, randomizing five N doses (0; 50; 100; 150 and 200 kg ha-1) in the main plot and four coloredcotton cultivars (BRS Safira, BRS Rubi, BRS Topázio and BRS Verde) in the subplots. Dry matter and N accumulations,agronomic, recovery, agrophysiological and physiological efficiencies in N utilization, and harvest index were evaluated.Cotton accumulates around 130 kg ha-1 of N along its cycle and directs 56.3% to seeds, 29% to leaves, 10.6% to stem and3.8% to fibers. Nitrogen agronomic efficiency and recovery efficiency decrease with increased N doses. The cultivar BRSTopázio is the most responsive to N fertilization and the cultivar BRS Verde is the least responsive.